Fifty five years of a feudal democracy - Rajwade, A.V. (2002)
The 55th anniversary of independence day should be an occasion to rejoice and celebrate. But is it? A brief perspective on where we stand in the comity of nations; what is happening in the country in terms of our governance, our mental attitude and stances. - Reproduced.
Keywords: Democracy; India - Politics and government; Politics and government